Fostering consumer engagement during an omnipresent victim crisis: understanding the role of values in pandemic-themed advertising - Lou, Chen (2023)
Many brands have launched pandemic-themed advertising campaigns, aiming to build rapport with their customers in this unprecedented moment. Yet it is challenging for brands to know how to communicate efficiently. To fill this gap, the current research aims to provide a systematic framework that could guide advertisers in designing pandemic-themed advertisements to stimulate consumer engagement on social media by examining the role of values in context-specific brand communications. In particular, we analyze a large corpus of 286 brand YouTube videos posted between the onset of the COVID-19 and the fall of 2020 through a combination of qualitative induction, coding, and big data analytics. The results demonstrate that brands can incorporate various values in their brand communications when the world is combating a victim crisis like the current pandemic. Our findings reveal that hedonism, universalism, conformity, security, and tradition values positively predict consumer engagement (i.e., commenting), whereas stimulation value negatively predicts consumer commenting. We develop a new type of victim crisis–omnipresent victim crisis–and offer a theorization of this sub-type of victim crisis to delineate the pandemic or crises alike (e.g., environmental issues) for future research. We further highlight the role of value embodiment in crisis communication and advertising literature and offer rich theoretical and practical implications.